2018
DOI: 10.3390/challe9020026
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Developmental Toxicants and Congenital Heart Disease in Urban and Rural Alberta, Canada

Abstract: The etiology of congenital heart defects (CHD) is not known for many affected patients. In the present study, we examined the association between industrial emissions and CHD in urban and rural Alberta. We acquired the emissions data reported in the Canadian National Pollutant Release Inventory (n = 18) and identified CHD patients born in Alberta from 2003-2010 (n = 2413). We identified three groups of emissions after principal component analysis: Groups 1, 2, and 3. The distribution of exposure to the postal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…We found strong negative associations with CHD in urban regions based on amounts emitted. In fact, in our previous study, [24] using a more precise exploratory approach, we found positive associations in both urban and rural postal codes exposed to the highest levels of Group 3 emissions [24].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We found strong negative associations with CHD in urban regions based on amounts emitted. In fact, in our previous study, [24] using a more precise exploratory approach, we found positive associations in both urban and rural postal codes exposed to the highest levels of Group 3 emissions [24].…”
Section: Discussionmentioning
confidence: 51%
“…In the current exploratory study, the most significant associations found with Groups 1 and 2 DTs remained regardless of using amounts or RS. Recently, using an inverse distance weighted (IDW) approach to understand the effect of maternal residential proximity to industrial facilities on the development of CHD [24], we identified that only the highest exposures to the three DTs Groups were associated with urban CHD while, in rural regions, associations occurred with Groups 1 and 3 DTs and not Group 2 DTs [24]. Despite the fact that rural regions had more facilities and emissions, their impact was larger in surrounding urban postal codes.…”
Section: Discussionmentioning
confidence: 99%
“…CHD is understood to be multifactorial in its etiology and the role of environmental chemical pollutants from various sources has gained increasing attention as well. We have recently shown that neighborhoods exposed to very high levels of multiple industrial chemical pollutants had an increased risk of CHD development [49,50]. In addition, other factors such as neighborhood characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty one of the 70 studies (30%) examined industrial chemical exposures through air or water and the development of CHD. Five of the 22 (23%) examined proximity to industrial sites as a proxy for exposure [61][62][63][64][65]. Seven studies (32%) used pollutant release and transfer registers (PRTR) [62][63][64][65][66][67][68][69].…”
Section: Outdoor Industrial Chemical Pollutionmentioning
confidence: 99%
“…Five of the 22 (23%) examined proximity to industrial sites as a proxy for exposure [61][62][63][64][65]. Seven studies (32%) used pollutant release and transfer registers (PRTR) [62][63][64][65][66][67][68][69]. Maternal residential proximity to hazardous waste sites [61,62], industries emitting organic compounds (e.g.…”
Section: Outdoor Industrial Chemical Pollutionmentioning
confidence: 99%